Physics schemes in the first version of NCEP operational hurricane analysis and forecast system (HAFS) - Wang, Weiguo; Han, Jongil; Shin, Junghoon; Chen, Xiaomin; Hazelton, Andrew; Zhu, Lin; Kim, Hyun-Sook; Li, Xu; Liu, Bin; Liu, Qingfu; Steffen, John; Sun, Ruiyu; et al. (Frontiers in Earth Science, 2024)
This document summarizes the physics schemes used in two configurations of the first version of the operational Hurricane Analysis and Forecast System (HAFSv1) at NOAA NCEP.The physics package in HAFSv1 is the same as that used in NCEP global forecast system (GFS) version 16 except for an additional microphysics scheme and modifications to sea surface roughness lengths, boundary layer scheme, and the entrainment rate in the deep convection scheme. Those modifications are specifically designed for improving the simulation of tropical cyclones (TCs). The two configurations of HAFSv1 mainly differ in the adopted microphysics schemes and TC-specific modifications in addition to model initialization. Experiments are made to highlight the impacts of TC-specific modifications and different microphysics schemes on HAFSv1 performance. Challenges and developmental plans of physics schemes for future versions of operational HAFS are discussed.